University doesn’t die yet: A perspective from Gorontalo State University (UNG) towards the social welfare in Gorontalo - Wolok, Eduart; Tanipu, Funco; Abbas, Tarmizi (2022)
In the Dark Academia: How University Die, Peter Fleming responses the current condition of university is already destructed by the impact of the bureaucratic and neoliberal structures of academia in which, has turned universities into a toxic place. He argues that university nowadays has loss its intellectual environment promised as guardian of reasons, philosophical openness and preserving pure inquiry of the public. Though Fleming is right in some cases but this argument cannot be taken for granted as well as generalized as the pin-point conclusion due to the lack of representations against universities which still hold their commitment to bring changes in the society. This paper argues that university does not die yet by exploring the role of Gorontalo State University as a key institution in providing services in societies and assisting public policies relating to the social and economical problems faced by the government. This research is based on the empirical studies with qualitative method during three-year of UNG’s involvement (2019-2021) toward the social welfare in Gorontalo. It is intended to see how the university, though facing many challenges both internal and external, but always keeping its eyes on the table to address challenges in the society.